2008
DOI: 10.1007/s00198-008-0646-7
|View full text |Cite
|
Sign up to set email alerts
|

Well-nourished cystic fibrosis patients have normal mineral density, but reduced cortical thickness at the forearm

Abstract: Adolescents and young adults with cystic fibrosis, presenting with only a slight degree of underweight, have at the radius a preserved bone mineral density but a reduced cortical thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Brookes and coworkers finding of larger bone deficits in post‐pubertal children with CF compared to pre‐pubertal children with CF are consistent with our results . Histomorphometric data suggest that adult patients with CF have lower cortical and trabecular bone mass, with low bone turnover and significant decreases in bone formation at the cellular level compared with healthy controls . Putman and colleagues reported that young adults with CF have smaller bone area and lower vBMD at the radius and tibia and have compromised bone microarchitecture at these two sites based on HR‐pQCT results .…”
Section: Discussionsupporting
confidence: 90%
“…Brookes and coworkers finding of larger bone deficits in post‐pubertal children with CF compared to pre‐pubertal children with CF are consistent with our results . Histomorphometric data suggest that adult patients with CF have lower cortical and trabecular bone mass, with low bone turnover and significant decreases in bone formation at the cellular level compared with healthy controls . Putman and colleagues reported that young adults with CF have smaller bone area and lower vBMD at the radius and tibia and have compromised bone microarchitecture at these two sites based on HR‐pQCT results .…”
Section: Discussionsupporting
confidence: 90%
“…However, these children had significantly lower mean pQCT trabecular vBMD Z-scores and significantly greater cortical vBMD Z-scores than the reference population [17]. Similar discrepancies between DXA and pQCT have been seen in studies of pediatric patients with Crohn disease and cystic fibrosis [18, 19]. …”
Section: Introductionmentioning
confidence: 78%
“…3 However, the true prevalence of CFRBD is likely much higher given that early disease is asymptomatic, adherence to screening guidelines is unknown, and commonly used screening tests may lack sensitivity in detecting early disease. 40,41 Reductions in BMD have been reported in children with CF, [42][43][44][45] but prevalence and severity of CFRBD increase with age and worsening general health status. Rates of reduced BMD in heterogeneous adult populations with CF range from 34 to 67%.…”
Section: Epidemiologymentioning
confidence: 99%